EFFECT OF LAND CONFIGURATION AND NUTRIENT MANAGEMENT ON GROWTH AND YIELD OF AFRICAN MARIGOLD VAR. PUNJAB GAINDA-1 UNDER SOUTH GUJARAT CONDITIONS - SANGEETHA PRIYA S.; DIPAL S. BHATT; CHAWLA S. L.; S. T. BHATT; G. D. PATEL (The Bioscan, 2020)
The experiment was laid out in split plot design with nine treatment combinations, consisting of three land configuration methods i.e. flat bed (L1), raised bed (L2) and ridge and furrow system (L3) and three doses of fertilizers i.e. 10 t FYM + 100% RDF/ha (N1), 8 t FYM + 80% RDF/ha (N2) and 6 t FYM + 60% RDF/ha (N3) replicated five times. The results revealed that maximum plant height (104.41 cm), plant spread (70.95 cm and 73.18 cm in N-S and E-W directions, respectively), more number of branches (11.91/plant), earlier flowering, prolonged flowering duration (99.67 days) and extended shelf life (4.40 days) with the flower yield of 14.62 t/ha were obtained from the plants grown on raised bed system. Moreover, plants receiving 10 t/ha FYM + 100% RDF (150:100:100 kg NPK/ha) improved the plant vegetative growth in terms of maximum plant height (98.46 cm), plant spread (65.75 cm and 68.53 cm in N-S and E-W directions, respectively), no. of branches (10.13), fresh and dry weight of plant (966.53 g and 473.60 g, respectively) and flowering characters like early flowering, maximum flower diameter (4.91 cm), weight of 10 flowers (61.55 g), no. of flowers (128.16/plant), longest flower duration (96.93 days) and maximum shelf life (3.73 days) with the flower yield being 500.68 g/plant and 11.30 t/ha.